Treatment with renin‐angiotensin system inhibitors and prognosis of heart failure with preserved ejection fraction: A propensity‐matched study in the community. Issue 6 (25th February 2019) - Egido, Jose J.; Gomez, Rocio; Romero, Sotero P.; Andrey, Jose L.; Ramirez, Daniel; Rodriguez, Ana; Pedrosa, Maria J.; Gomez, Francisco
Abstract: Aims: There is currently no consensus on the effect of treatment with angiotensin‐converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs), on the prognosis of patients with heart failure and preserved ejection fraction (HFpEF). Therefore, we have analysed the relationship of commencing treatment with ACEIs or ARBs and the prognosis of patients with incident HFpEF. Methods: Retrospective study over 15 years on 3864 patients with HFpEF (GAMIC cohort). Main outcomes were mortality (all‐cause and cardiovascular) and hospitalisations for HF. The independent relationship between CT‐RASIs and the prognosis, stratifying patients for cardiovascular comorbidity after propensity score‐matching was analysed. Results: During a median follow‐up of 7.94 years, 2960 died (76.6%) and 3138 were hospitalised (81.2%). Therapy with RASIs was associated with a lower mortality, all‐cause (RR [95% CI] for ACEIs: 0.76 [0.66‐0.86], and RR for ARBs: 0.88 [0.80‐0.96]; P < 0.001 in both cases), and cardiovascular (RR for ACEIs: 0.72 [0.66‐0.78], and RR for ARBs: 0.87 [0.80‐0.94]; P < 0.001), a lower hospitalisation rate (RR for ACEIs: 0.82 [0.74‐0.90], and RR for ARBs: 0.90 [0.82‐0.98]; P < 0.001), and a lower 30‐day readmission rate (RR for ACEIs: 0.66 [0.60‐0.73], and RR for ARBs: 0.86 [0.75‐0.97]; P < 0.001), after adjustment for the propensity to take RASIs or other medications, comorbidities and other potential confounders. Results on the effect of ARBs are compromised by the small number of patients. Analyses of recurrent hospitalisations gave larger treatment benefits than time‐to‐first‐event analyses. Conclusion: In this propensity‐matched study, commencing treatment with ACEIs is associated with an improved prognosis of patients newly diagnosed with incident HFpEF.